Construindo meninas com Capricho: análise dos modelos de feminilidades construídos a partir da marca Capricho na seção Instagram da leitora - Mendes, Shamara Paiva (2018)
This research tries to analyze, under the frankfutian theoretical bias, the constructions of models of femininities produced and divulged through the contents of Capricho, in the Abril publisher website, from the Instagram section of the Reader, in order to understand how the desconstructions and reconstructions of femininities forged in these spaces. Capricho, as a brand, will produce new meanings and delineate the image of complicity between consumer and brand, creating a process of identifying consumers to the models of feminities that are proclaimed by it. A total of 187 photographs of the Reader's Instagram section were analyzed between May 2015 and May 2016, as well as an analysis of the prints of the section on Abril's website. The positions and cutouts made by Capricho were problematized from the material made available by the youngsters and used in the section. From the analysis it was possible to identify models of femininity and body with a pattern about what was expected of the publications of the young women. Initially, we chose to group the publications from the types of photographs into a cataloging sheet that allowed us to know the quantity of photographs selected by type, such as selfies, accompanied photos, landscapes, food, animals, etc. From the cataloging sheet it was possible to indicate which images and texts of the section fit the objectives of the research. After the systematization and analysis of the material, we identified that the profiles of the young are cataloged and exposed from the prerogative of adequacy to the ideas of the brand and that the criteria of publication make direct reference to a slim and beautiful body. There is also the image that Capricho legitimizes female empowerment and that the discourses, of many of these profiles, say of a search for acceptance of one's own body and autonomy, yet this discourse of empowerment is lost amid the dictates of having a " healthy "and lean, accepted by the girl as" is ", but stoned by exercises, diets and filters that highlight the parts of the body that would not need adjustments, such as eyes, hair, legs. The fragmentations of the body are present in many selected photographs and show the body and the feminities marked by servility and dependence on the models propagated therein in a constant effort for adequacy. Finally, we note that although there is attempted subjection.